Dialogen over België Herinneringen, beelden, opvattingen - Brems, Elke; Beyen, Marnix; Bazan, Ariane; Luminet, Olivier; Rosoux, Valerie (Leuven University Press, 2020)
"What events, places and figures linger in the memory of eighteen prominent Belgians when they think of their country? French-speaking and Dutch-speaking academics sought an answer to this question for several years. They organized meetings with Belgian duos from various social domains: the journalists Nina Verhaeghe and Christian Laporte, politicians Herman Van Rompuy and Philippe Moureaux, poets Dirk Van Bastelaere and Laurence Vielle, directors Jan Verheyen and Adil El Arbi, writers Kristien Hemmerechts and Vincent Engel, athletes Laurence Rase and Jean-Michel Saive, the businessmen Yves Noël & Christ'l Joris, the syndicalists Caroline Copers and Felipe Van Keirsbilck, and the imam and Islam teacher Brahim Laytouss and theologian Myriam Tonus.